2011
DOI: 10.1177/1471301211416613
|View full text |Cite
|
Sign up to set email alerts
|

The staff's view on dementia and the care in three cultures: A qualitative study in France, Portugal and Sweden

Abstract: This article discusses the staff's view on dementia and its impact on the care delivered arising out of a qualitative comparative study focusing on long-term care of older people in France, Portugal and Sweden. The aim was to explore the staff's view on the illness dementia; on older people suffering from dementia; the care provided and the impact of various views on the care. The care was studied through observations at 22 care settings in the three countries and the staff's attitudes were explored by means o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…; Nichols et al., ; Yong & Manthorpe, ), one study included care workers only (Xiao et al., ). Two studies included other healthcare professions, of which one study included qualified nurses, a care worker and a physiotherapist (Egede‐Nissen et al., ), and one study included doctors, therapists, dieticians, social workers, qualified nurses and care workers (Emilsson, ). The majority of studies ( n = 6) applied semi‐structured interviews (Antelius & Kiwi, ; Boughtwood et al., ; Egede‐Nissen et al., ; Emilsson, ; Xiao et al., ; Yong & Manthorpe, ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…; Nichols et al., ; Yong & Manthorpe, ), one study included care workers only (Xiao et al., ). Two studies included other healthcare professions, of which one study included qualified nurses, a care worker and a physiotherapist (Egede‐Nissen et al., ), and one study included doctors, therapists, dieticians, social workers, qualified nurses and care workers (Emilsson, ). The majority of studies ( n = 6) applied semi‐structured interviews (Antelius & Kiwi, ; Boughtwood et al., ; Egede‐Nissen et al., ; Emilsson, ; Xiao et al., ; Yong & Manthorpe, ).…”
Section: Resultsmentioning
confidence: 99%
“…() included semi‐structured questionnaires and a workshop. All studies reported an underlying philosophy that guided their methodological approach, which ranged from ethnography (Antelius & Kiwi, ), modified framework analysis (Boughtwood et al., ), hermeneutic phenomenology (Egede‐Nissen et al., ), content analysis (Emilsson, ), interpretative phenomenology (Yong & Manthorpe, ) and Gadamer's hermeneutics (Xiao et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations